1981
DOI: 10.1136/thx.36.4.308
|View full text |Cite
|
Sign up to set email alerts
|

Ketotifen in atopic asthma and exercise-induced asthma.

Abstract: The efficacy of ketotifen, a tricyclic benzocycloheptathiophene derivative, was assessed in an outpatient clinical trial and in a group of 12 asthmatic subjects with exerciseinduced asthma. Subjects in the outpatient trial had mild asthma and consisted of two groups: a group of 24 atopic asthmatics with at least one positive skin test reaction and with an associated history of bronchial reactivity to at least one allergen; and a group of eight asthmatics with one or more positive skin prick tests but no bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Antihistamines may be helpful in the treatment of FDEIA and may be useful in the prevention of urticaria or angioedema 5 . Ketotifen is an orally active tricyclic benzocyclo-heptathiophene derivative and thus may be a useful medication in the treatment and prevention of allergic responses 16 . Ketotifen is a potent H1 receptor antagonist which has properties of mast cell stabilization and anti-inflammatory capabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antihistamines may be helpful in the treatment of FDEIA and may be useful in the prevention of urticaria or angioedema 5 . Ketotifen is an orally active tricyclic benzocyclo-heptathiophene derivative and thus may be a useful medication in the treatment and prevention of allergic responses 16 . Ketotifen is a potent H1 receptor antagonist which has properties of mast cell stabilization and anti-inflammatory capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Ketotifen also has other anti-inflammatory properties, which include reduced eosinophilic chemotaxis in eosinophilia and diminished production of eotaxin and expression of CD29 in epithelial cells 17 . Previous reports have not reached a consensus on the efficacy of ketotifen in preventing EIA [16][17][18] . In the case reported herein, however, we observed that 1 mg of ketotifen 2 hours before wheat ingestion prevented FDEIA.…”
Section: Discussionmentioning
confidence: 99%
“…These include oxatomide (78), RS7640 a xanthone (82), doxantrazole (67) and FPL57787 an oral chromone (88). Oral ketotifen does not inhibit EIA (6,66).…”
Section: Drugs Whzch Preuent Eiamentioning
confidence: 99%
“…Several studies have demonstrated inhibition by ketotifen ofhistamineinduced (Craps et al, 1978) and allergen-induced (Craps et al, 1978;Palmen, 1983) bronchoconstriction, but reports of its efficacy in exerciseinduced asthma (EIA) are conflicting (Craps et al, 1978;Dorward & Patel, 1982;Petheram et al, 1981;Kennedy etal., 1980;Lilja etal., 1983). Most of these studies were performed after 3 weeks or less of treatment with ketotifen and it has been suggested that the maximum effect may not be achieved until 5 weeks after treatment has been commenced (Gobel, 1978).…”
Section: Introductionmentioning
confidence: 99%